Radioiodination of Murine Anti-Alphafoetoprotein E.9 Monoclonal Antibody and its F(ab’)2 Fragment for the Diagnosis of Hepatocellular Carcinoma - Beyers, M.; Aspinall, S.; Conradie, J. D.; Fourie, P. J. (Nuklearmedizin - NuclearMedicine, 1988)
The high incidence of hepatocellular carcinoma amongst certain population groups of Southern Africa made feasible the investigation of a radiolabeled monoclonal anti-alphafoetoprotein as a radioimmunodiagnostic agent for this disease. This paper reports the preclinical trials with monoclonal anti-alphafoetoprotein E.9 (anti-AFP) and its F(ab’)2 fragment after radiolabelling with 131l. Various radioiodinations were tried. The best results were obtained with the lodogen and Bolton-Hunter methods.1311 from only one of the sources tested gave an 131 l-labelled anti-AFP with meaningful immunoreactivity. It was shown by means of gamma-camera scans and monitoring of radioactivity in individual organs that 131l-anti-AFP and the 131l-anti-AFP F(ab’)2 fragments did not accumulate abnormally in any organ(s) in healthy animals. The correlation in healthy mice of the biodistribution of 125l human IgG to 131 l-anti-AFP, and 125l human IgG to 131l-F(ab’)2 was good. Human hepatoma xenografts in athymic mice showed uptake of131 l-anti-AFP and the 131l-F(ab’)2 fragment. The uptake of 131l-F(ab’)2 was improved by liver background subtraction. There was correlation between circulatory alphafoetoprotein concentrations and tumour uptake of 131l-F(ab’)2 in tumour-bearing athymic mice and a definite relationship was found between tumour size and radiolabelled antibody and the F(ab’)2 fragment. After the biological action of the131 l-anti-AFP and the 131l-F(ab’)2 fragment was known, sterile pyrogen-free consignments were supplied for clinical trials in humans on a regular basis.Die hohe Inzidenz des hepatozellulärenKarzinoms unter bestimmtenBevölkerungsgruppen des südlichenAfrika ließ die Untersuchung von radioaktivmarkiertem monoklonalemAntialphafetoprotein als Radioimmundiagnostikumfür diese Erkrankungsinnvoll erscheinen. In dieserArbeit wird über präklinische Versuchemit monoklonalem AntialphafetoproteinE.9 (Anti-AFP) und seinesF(ab’)2-Fragments nach Markierungmit 131J berichtet. Verschiedene Methodender Radiojodierung wurdengetestet. Die besten Ergebnisse wurdenmit der Jodogen-Methode unddem Bolton-Hunter-Verfahren erreicht.131J verschiedener Herstellerwurde getestet. Nur 131J aus einer dergeprüften Quellen ergab eine 131J-Anti-AFP-Markierung mit brauchbarerImmunreaktivität. Mit Hilfe vonGamma-Kamera-Szintigrammen undmit Radioaktivitätsmessungen in einzelnenOrganen wurde gezeigt, daß131J-Anti-AFP und das 131J-Anti-AFPF(ab’)2-Fragment sich in keinemOrgan gesunder Tiere abnormal anreicherte.Die Korrelation der Bioverteilungvon 125J-markiertem humanemund mit 125J-markiertem humanemIgG zu 131J-markiertem F(ab’)2 war ingesunden Mäusen gut. MenschlicheHepatom-Xenotransplantationen inathymischen Mäusen zeigten eine Anreicherungdes 131J-markierten Anti-AFP und des 131J-F(ab’)2-Fragments.Die Aufnahme des 131J-F(ab’)2 wurdenach Leberhintergrundsubtraktionbesser dargestellt. Eine Abhängigkeitzwischen Blutalphafetoproteinkonzentrationund dem Tumoruptake von131J-F(ab’)2 in tumortragenden Nacktmäusenund ein bestimmter Zusammenhangzwischen der Tumorgrößeund dem radioaktiv markierten Antikörperund dem F(ab’)2-Fragmenwurde nachgewiesen. Nachdem diebiologische Wirkung des 131J-Anti-AFP und des 131J-F(ab’)2-Fragmentsbekannt war, wurden sterile pyrogenfreieChargen für klinische Prüfungenam Menschen regelmäßig hergestellt.